Design, Synthesis and Properties of Novel BODIPY Dyes With Styryl as π‐Bridge at 3, 5‐Positions. Issue 30 (11th August 2020) - Xu, Jian; Zong, Qiao; Peng, Shengming; Liao, Junxu; Zhao, Hongbin; Kong, Haojun; Xu, Junhao
Abstract: Three novel D−A‐D type small molecules Boron Fluoride Complexed Dipyridylmethine (BODIPY), BDP1‐3, linked through styryl with various strong electron donor units, such as carbazole, phenothiazine, fluorene, were designed and synthesized. The results suggest that the donor have significant effect on their photophysical and electrochemical properties. All these BDP1‐3 exhibit the obvious broader and red‐shifted absorption, the molecular absorption spectrum to range of 300–700 nm and the high molar extinction coefficients. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMU) energy level of them are calculated to be −5.18 eV and −3.21 eV, respectively. The broad and intense absorption, suitable HOMO‐LUMO energy levels make BDP1‐3 potential candidates for light‐harvesting and photovoltaic application. Abstract : The present work presents a new structure of the modification of Boron Fluoride Complexed Dipyridylmethine (BODIPY) at 3, 5‐positions. Herein, carbazole, phenothiazine, fluorene were introduced to 3, 5‐positions BODIPYs as the electron‐donor, by Knoevenagel condensation. The UV‐vis absorption, electrochemical properties and theoretical calculation were considered to check the availability of the prepared structure for light collection and photovoltaic application.